Primary cutaneous peripheral T‐cell lymphoma, not otherwise specified: results of a multicentre European Organization for Research and Treatment of Cancer (EORTC) cutaneous lymphoma taskforce study on the clinico‐pathological and prognostic features. (22nd December 2020) - Kempf, W.; Mitteldorf, C.; Battistella, M.; Willemze, R.; Cerroni, L.; Santucci, M.; Geissinger, E.; Jansen, P.; Vermeer, M.H.; Marschalko, M.; Papadavid, E.; Piris, M.A.; et al.
Abstract: Background: Cutaneous peripheral T‐cell lymphoma, not otherwise specified (PTL NOS) is an aggressive, but poorly characterized neoplasm. Objectives: The European Organization for Research and Treatment of Cancer cutaneous lymphoma taskforce (EORTC CLTF) investigated 33 biopsies of 30 patients with primary cutaneous PTL NOS to analyse their clinical, histological, immunophenotypic features and outcome. Methods: Retrospective analysis of clinical data and histopathological features by an expert panel. Results: Cutaneous PTL NOS manifested clinically either with solitary or disseminated rapidly grown ulcerated tumours or disseminated papulo‐nodular lesions. Histologically, a mostly diffuse or nodular infiltrate in the dermis and often extending into the subcutis was found. Epidermotropism was rarely present and only mild and focal. Unusual phenotypes were frequent, e.g. CD3 + /CD4 − /CD8 − and CD3 + /CD4 + /CD8 + . Moreover, 18% of the cases exhibited an aberrant expression of the B‐cell marker CD20 by the tumour cells. All solitary tumours were located on the limbs and presented a high expression of GATA‐3 but this did not correlate with outcome and therefore could not serve as a prognostic factor. The prognosis was shown to be generally poor with 10 of 30 patients (33%) dying of lymphoma within the follow‐up of 36 months (mean value; range 3–144). The survival rates were 61% after 3 years (CI, 43–85%) and 54% after 5 years (CI, 36–81%). Small to medium‐sized morphology of tumour cells was associated with a better outcome than medium to large or large tumour cells. Age, gender, clinical stage, CD4/CD8 phenotype and GATA‐3 expression were not associated with prognosis. Chemotherapy was the most common treatment modality, but surgical excision and/or radiotherapy may represent an appropriate first‐line treatment for solitary lesions. Conclusions: Cutaneous PTL NOS shows an aggressive course in most patients independent of initial presentation, age and phenotype. Cytomorphology was identified as a prognostic factor. The data indicate a need for more effective treatment modalities in PTL NOS.